Integrasi Model Problem Based Learning Berorientasi Etnomatematika dalam Meningkatkan Kemampuan Berpikir Kritis Siswa - Putra, I Kadek Aditia; Parmiti, Desak Putu; Dantes, Nyoman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze and synthesize empirical evidence regarding the implementation and effectiveness of the ethnomathematics-oriented Problem-Based Learning (PBL) model in improving students' critical thinking skills. The method used was a Systematic Literature Review (SLR) with the collection of 20 primary study articles from reputable national and international databases (Sinta and Scopus). The results of the qualitative synthesis indicate that the implementation of this PBL model focuses on the use of local cultural objects or practices (e.g., temple architecture, batik patterns, or traditional houses) as authentic problems in the problem orientation and investigation stages of PBL. Based on the analysis of the 20 articles, the quantitative Normalized Gain analysis of the selected studies consistently shows an increase in critical thinking skills in the moderate to high category (0.62–0.81). It can be concluded that the synergy between PBL as a methodological structure and ethnomathematics as an authentic context is a highly effective learning strategy and has been empirically proven in developing students' analytical, inferential, and evaluation skills, which are the core of critical thinking. Keywords: PBL, Ethnomathematics, Critical Thinking, Literature Review